Analisis Faktor-Faktor Yang Mempengaruhi Penerimaan Opini Audit Going Concern Dalam Perusahaan Manufaktur Di Indonesia Tahun 2012-2014 - Kusumawati, Nurul Tahta; , Fauzan, S.E., M.Si (2016)
This research aims to predict the effect of debt default, the financial condition of the company, opinion shopping, quality audit, the audit opinion of the previous year, and the size of the company going concern audit opinion. In this research, the type of used data is quantitative data with a population of 66 companies listed in the Indonesia Stock Exchange in 2012-2014. The analytical method used is logistic regression analysis with the study sample was 22 companies were selected based on purposive sampling method during the third period. Based on the results of the analysis can be concluded that the debt default no significant effect on revenues going concern audit opinion, the financial condition of the company does not significantly influence acceptance of going concern audit opinion, opinion shopping significant effect on revenues going concern audit opinion, audit quality is not significantly influence the acceptance going concern audit opinion, the previous year's audit opinion significantly influence the going concern audit opinion, and the size of the company does not have a significant effect on the going-concern audit opinion. Keywords: debt default, the financial condition of the company, opinion shopping, quality audit, the audit opinion of the previous year, the size of the company, and going concern audit opinion.